The changes of umami substances and influencing factors in preserved egg yolk: pH, endogenous protease, and proteinaceous substance - Gao, Binghong; Hu, Xiaobo; Xue, Hui; Li, Ruiling; Liu, Huilan; Han, Tianfeng; Tu, Yonggang; Zhao, Yan (Frontiers in Nutrition, 2022)
The study investigated the changes of nucleotides, succinic acid, and free amino acids amounts in yolk and the causes leading to the changes after pickling to uncover the fundamental umami component of preserved egg yolk. The findings demonstrated that while the contents of 5′-adenosine monophosphate (AMP), 5′-cytidine monophosphate (CMP), 5′-guanosine monophosphate (GMP), 5′-uridine monophosphate (UMP), and succinic acid increased after slightly decreasing aspartic acid (Asp) content in preserved egg yolk increased gradually. The contents of 5′-inosine monophosphate (IMP) and other free amino acids were gradually decreased. Comparing the taste activity value (TAV), it was found that the single umami substance, succinic acid, played a key role in inducing the umami taste. In combination with the Spearman correlation analysis, it was shown that the proteinaceous substance, which is the most significant umami component in preserved egg yolk, tended to condense first and subsequently disintegrate in an alkaline environment. The orthogonal partial least squares analysis (OPLS) found that pH was also affected by the changes in proteinaceous substance. These findings offer suggestions for enhancing the pickling procedure and investigating the optimal pickling period for preserved eggs.